Institutionalisation of co-production in the reform of a public enterprise: insights from the Philippines. Issue 2 (17th February 2020) - Ledesma-Gumasing, Rhea; Zimmermann, Willi
ABSTRACT: Research on the institutionalisation of co-production achieved through deliberation is a current research gap in the Global South. This qualitative case study of the Naga City People's Mall (NCPM) in the Philippines was based on semi-structured interviews with 29 key stakeholders, published documents and observations in the market place. The study reconstructs the triggers and procedures leading to institutional and organisational changes in the form of public-private co-production. The case presents a strong argument that co-production can be successful despite the complex process of deliberation – an important element in ensuring that institutions remain relevant and results sustained.